2022
DOI: 10.3390/biom12060818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olfactory Mucosa Stem/Stromal Cell and Olfactory Ensheating Cells Secretome on Peripheral Nerve Regeneration

Abstract: Cell secretome has been explored as a cell-free technique with high scientific and medical interest for Regenerative Medicine. In this work, the secretome produced and collected from Olfactory Mucosa Mesenchymal Stem Cells and Olfactory Ensheating Cells was analyzed and therapeutically applied to promote peripheral nerve regeneration. The analysis of the conditioned medium revealed the production and secretion of several factors with immunomodulatory functions, capable of intervening beneficially in the phases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The therapeutic application of MSCs demands the characterization of stem cell products based on their molecular and cellular characteristics[ 47 ]. The paracrine activity of MSCs via the secretome and their unique stem cell features such as proangiogenic, anti-inflammatory, immunomodulatory, and antioxidant potential are the mechanisms behind the utilization of MSCs for therapeutic purposes[ 48 , 49 ]. Studies have observed the significant therapeutic promise of MSCs to treat fatal disorders in numerous clinical trials[ 50 - 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic application of MSCs demands the characterization of stem cell products based on their molecular and cellular characteristics[ 47 ]. The paracrine activity of MSCs via the secretome and their unique stem cell features such as proangiogenic, anti-inflammatory, immunomodulatory, and antioxidant potential are the mechanisms behind the utilization of MSCs for therapeutic purposes[ 48 , 49 ]. Studies have observed the significant therapeutic promise of MSCs to treat fatal disorders in numerous clinical trials[ 50 - 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The imaging approach has been sparsely used and has only recently gained more importance in this area as dramatic advances are observed in the quality of the techniques that can be used. In traditional and smaller animal models such as rodents, some commonly used imaging approaches include techniques such as transgenic labeling, nervous stereology, and muscle histomorphometry [ 6 , 11 ]. In larger animal models, however, although these routine techniques can and should also be used, other methods closer to those likely to be applied in real clinical settings, such as ultrasound, are also an option that should be considered [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of works in which new therapeutic alternatives for the treatment of PNI are studied are based on more traditional animal models, such as rodents [ 3 ], in which significant advances have been achieved in the establishment of new innovative treatments, namely in the fields of regenerative medicine and based on cell-based therapies and application of biomaterials [ 4 ]. For instance, previously, our research group has developed several new therapeutic combinations based on the use of innovative biomaterials and mesenchymal stem cell-derived products, which have demonstrated good results when applied in the rat model [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In two previous studies on rat models of peripheral nerve injury, we demonstrated the efficacy of OE-MSCs in improving motor functional recovery of the lower limb or face (Bonnet et al, 2020;Alvites et al, 2022). To assess whether the clinical grade cultured OE-MSCs stimulate axonal regrowth through extruded factors, a N2a cell line was cultivated with a 50:50 mixture of fresh differentiation medium and the conditioned medium collected from a 24 h or a 48 h-long culture of OE-MSCs.…”
Section: Clinical Grade Olfactory Ecto-mesenchymal Stem Cell-conditio...mentioning
confidence: 99%